2022
DOI: 10.5194/acp-22-14037-2022
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric biogenic volatile organic compounds in the Alaskan Arctic tundra: constraints from measurements at Toolik Field Station

Abstract: Abstract. The Arctic is a climatically sensitive region that has experienced warming at almost 3 times the global average rate in recent decades, leading to an increase in Arctic greenness and a greater abundance of plants that emit biogenic volatile organic compounds (BVOCs). These changes in atmospheric emissions are expected to significantly modify the overall oxidative chemistry of the region and lead to changes in VOC composition and abundance, with implications for atmospheric processes. Nonetheless, obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 87 publications
3
9
0
Order By: Relevance
“…8 are not due to near-field production in BB, though enhancement in much more aged plumes (>2 days) has been observed. 102,103 As methanol and acetone are known to be major primary emissions and secondary products from biogenic sources, 12,31,102,104–106 we hypothesize that their strong correlation with FA during WE-CAN and FIREX-AQ indicates that a portion of the observed FA may be of biogenic origin, though the long atmospheric lifetimes of all three species (>2 days) likely also play a role in why they are well correlated with each other.…”
Section: Geos-chem Representation Of Fa and Aa During We-can And Fire...mentioning
confidence: 98%
See 1 more Smart Citation
“…8 are not due to near-field production in BB, though enhancement in much more aged plumes (>2 days) has been observed. 102,103 As methanol and acetone are known to be major primary emissions and secondary products from biogenic sources, 12,31,102,104–106 we hypothesize that their strong correlation with FA during WE-CAN and FIREX-AQ indicates that a portion of the observed FA may be of biogenic origin, though the long atmospheric lifetimes of all three species (>2 days) likely also play a role in why they are well correlated with each other.…”
Section: Geos-chem Representation Of Fa and Aa During We-can And Fire...mentioning
confidence: 98%
“…This low model bias is most pronounced in biogenic source regions, 7,8 including United States (U.S.) deciduous forests, 9,10 boreal forests, 11 tropical forests, 6 and in the Arctic tundra. 12 Additionally, models typically fail to capture FA and AA enhancements in plumes from mixed anthropogenic sources 13,14 and in biomass burning (BB) impacted regions, [15][16][17] indicating potential missing primary and/or secondary sources in smoke. In this work, we investigate emissions, secondary productions, and model representations of FA and AA in the western U.S. during two wildre seasons, using measurements made during the WE-CAN (Western Wildre Experiment for Cloud Chemistry, Aerosol Absorption, and Nitrogen) and FIREX-AQ (Fire Inuence on Regional to Global Environments and Air Quality) eld campaigns.…”
Section: Introductionmentioning
confidence: 99%
“…is a prevalent source of isoprene in high latitude ecosystems (Li et al, 2023;Potosnak et al, 2013;Simin et al, 2021). Recent whole-ecosystem measurements suggest that the temperature response of isoprene emissions in high-latitude tundra ecosystems is stronger than what current isoprene emission models predict (Angot et al, 2020;Holst et al, 2010;Li et al, 2023;Seco et al, 2020Seco et al, , 2022Selimovic et al, 2022;Vettikkat et al, 2023). In contrast, leaf/branch-level studies showed that the hourly temperature response of Arctic willow species (Salix pulchra Cham.…”
Section: Supporting Informationmentioning
confidence: 99%
“…The model-satellite discrepancies outside wildfire areas could be also due to model underestimates of oxygenated VOCs (OVOCs), biogenic VOC emissions and biases in satellite HCHO retrieval products. For example, Selimovic et al (2022) found that GEOS-Chem underestimates OVOCs, including HCHO, by a factor of 3-12 at Toolik Field Station in northern Alaska. Stavrakou et al (2015) show model underestimations of biogenic isoprene emissions and wildfire emissions over eastern Europe and Alaska.…”
Section: Evaluation Of the Spatial Distribution Of Hcho Vcd And Bvoc ...mentioning
confidence: 99%
“…This BVOC speciation appears to be different in the boreal forests in Alaska, northern Canada and eastern Siberia, where isoprene appears to be the most abundant BVOC species (Blake et al, 1992;Timkovsky et al, 2010;Zhao et al, 2022). BVOC measurements in tundra systems show a very strong positive temperature dependence for isoprene fluxes over Greenland (Vedel-Petersen et al, 2015;Kramshøj et al, 2016;Lindwall et al, 2016a), northern Sweden (Faubert et al, 2010;Tang et al, 2016) and the Alaska North Slope (Potosnak et al, 2013;Angot et al, 2020;Selimovic et al, 2022).…”
mentioning
confidence: 99%